TIPE GROUP INVESTIGATION (GI) PADA MATERI MAKRO MOLEKUL (POLIMER) - SIREGAR, ROMA MINDO (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study aims to determine whether there is a relationship between the Group Investigation (GI) type learning model towards learning motivation and chemistry learning outcomes in polymeric materials. The research method used is quantitative research that is correlational. Sampling in this study was students of class XII IPA Catholic High School Sibolga. The results of this study are that there is a significant relationship between the learning model of the Group Investigation (GI) type and the learning outcomes of chemistry in the polymeric material of class XII IPA students at Sibolga Catholic High School at 0.316 with a low category.